Exploring the Implementation and Challenges of Character Education in Junior High School Mathematics: A Mixed-Methods Study in Indonesia - Rahayu, Adellia Tri; Andini, Dea Gusera; Amanda, Irma Nadia Putri; Qolbi, Rizma Nurfajriah; Aisyah, Nyimas; Susanti, Elsa (SEAMEO Regional Centre for QITEP in Mathematics, 2025)
Character education is one of the government's flagship programs today. As part of national education, character education is expected to instil character values at all levels of education, including in mathematics, and examine how character values are applied in mathematics learning in schools from the perspective of teachers and students. Using a qualitative descriptive approach, data were collected through structured and unstructured questions asked to students at one of the selected SMA Negeri 1 Palembang. Participants consisted of 88 students, namely 58 females and 30 males, and 1 teacher who was interviewed in the data collection stage to provide views from the educator's perspective. Participants were selected purposively to ensure contextual relevance. The results of the study showed that attitude was the most dominant factor influencing students in mathematics learning, while other factors that also influenced were the role of teachers, student activity in learning, and student inactivity. To assess the effectiveness of character education in mathematics learning, this study used an exploratory learning-based approach with in-depth assessment and strengthened collaboration, so that teachers were better able to instil character values directly and indirectly.